Queuing System Design On Android-Based Bank Teller Method Using Multi Channel - Single Phase: Queuing System Design On Android-Based Bank Teller Method Using Multi Channel - Single Phase - Arman Mubarokh; Mohammad Iwan Wahyuddin; Sari Ningsih (Institute of Computer Science (IOCS), 2020)
This research was conducted because of the frequent problems of queuing at company services such as banks, so that there are things that are not profitable between customers and banks. This problem Generally Occurs Because it is the caused by the need for services performed by customers that are exceeding capacity, the which makes the customer have to wait in line for some time to be served. The time-consuming queuing system will harm both parties for the customer and the bank. The purpose of this research is to create a mobile-based online queuing system using the mobile web applications and to get a queue number, so that customers no longer have to come in advance to the queue and can use the time to queue practically. This application is expected to reduce the long queues on bank services and the service process works better and more efficiently. It is hoped that this system will provide benefits and impact on the satisfaction of customers and the bank. This system implements a single phase roomates multi-channel method can use more than one teller and only has one queue number. Thus Spake the teller can serve the queue number without having to wait for other tellers to serve the customer, so that it can reduce the queue that Occurs in the bank.